Technical Efficiency Of Arabian And East African Container Terminals. - Al-Eraqi, Ahmed Salem; Barros, Carlos Pestana; Mustaffa, Adli; Khader, Ahmad Tajudin (2007)
In this paper the efficiency and performance is evaluated the terminal container for 22 seaports in the region of East Africa and the Middle East. The aim of our study is to compare container terminals situated on the maritime trade road between the East and the West. These are considered as middle-distance ports at which goods from Europe and Far East/Australia can be exchanged and transshipped to all countries in the Middle East and East Africa.